Gambaran Activity of Daily Living pada pasien post operasi - Ramayana Lestari Dewi; Mulia Hakam; Murtaqib Murtaqib (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
One of the most postoperative problems is limited movement. The impact of limited movement affects a person's dependence on doing activities of daily living (ADL). The purpose of this study was to determine the Activity of Daily Living Description of postoperative patients. This study is a descriptive research design. Samples were obtained using a consecutive sampling technique with a total of 57 respondents who fulfilled the inclusion criteria. The instrument used in this study was the CDS questionnaire. The results of this study showed most of the respondents have partially dependent ADL (56,1%); the ADL of great extent care dependent was 31,6% and 1.8% postoperative patients in the category of completely care dependent. The ADL of mind care dependent was 7% and almost independent was 3,5%. Success in fulfilling ADL needs that can be done by patients independently will accelerate the recovery period and improve the quality of life for postoperative patients. Therefore the role of nurses is very important in fostering the independence of postoperative patients so that postoperative patient ADL dependence is reduced or is able to do ADL independently.